HER2 status of CTCs by peptide-functionalized nanoparticles as the diagnostic biomarker of breast cancer and predicting the efficacy of anti-HER2 treatment - Wang, Mengting; Liu, Yaxin; Shao, Bin; Liu, Xiaoran; Hu, Zhiyuan; Wang, Chen; Li, Huiping; Zhu, Ling; Li, Ping; Yang, Yanlian (Frontiers in Bioengineering and Biotechnology, 2022)
Efficacy of anti-human epidermal growth factor receptor 2 (HER2) treatment is impacted by tissue-based evaluation bias due to tumor heterogeneity and dynamic changes of HER2 in breast cancer. Circulating tumor cell (CTC)-based HER2 phenotyping provides integral and real-time assessment, benefiting accurate HER2 diagnosis. This study developed a semi-quantitative fluorescent evaluation system of HER2 immunostaining on CTCs by peptide-functionalized magnetic nanoparticles (Pep@MNPs) and immunocytochemistry (ICC). 52 newly-diagnosed advanced breast cancer patients were enrolled for blood samples before and/or after first-line treatment, including 24 patients who were diagnosed with HER2+ tumors and treated with anti-HER2 drugs. We enumerated CTCs and assessed levels of HER2 expression on CTCs in 2.0 mL whole blood. Enumerating CTCs at baseline could distinguish cancer patients (sensitivity, 69.2%; specificity, 100%). 80.8% (42/52) of patients had at least one CTCs before therapy. Patients with < 3 CTCs at baseline had significantly longer progression-free survival (medians, 19.4 vs 9.2 months; log-rank p = 0.046) and overall survival (medians, not yet reached; log-rank p = 0.049) than those with ≥ 3 CTCs. Both HER2+ and HER2-low patients could be detected with HER2 overexpression on CTCs (CTC-HER2+) (52.6%, 44.4%, respectively), whereas all the HER2-negative patients had no CTC-HER2+ phenotype. Among HER2+ patients with ≥ 3 CTCs at baseline, objective response only appeared in pretherapeutic CTC-HER2+ cohort (60.0%), rather than in CTC-HER2– cohort (0.0%) (p = 0.034). In conclusion, we demonstrate the significance of CTC enumeration in diagnosis and prognosis of first-line advanced breast cancer, and highlight the value of CTC-HER2 status in predicting efficacy of anti-HER2 treatment.